Ellipsometric analysis of concentration gradients induced in semiconductor crystals by pulsed laser induced epitaxy - Schlipf, Jon; Martin, Elena; Stchakovsky, Michel; Benedetti, Alessandro; Fischer, Inga A.; Schulze, Jörg; Chiussi, Stefano (Journal of Vacuum Science & Technology B, Nanotechnology and Microelectronics, 2019)
The authors report a novel approach to analyze the behavior of pulsed-laser-induced epitaxy on group-IV semiconductors by spectroscopic ellipsometry measurements and finite-element modeling of the thermo- and hydrodynamic behavior. Gradient-composition epitaxial crystals are obtained from previously atomically sharp heteroepitaxial samples through optically monitored processing with UV excimer laser pulses. Spectroscopic ellipsometry is employed to determine the composition gradient of the semiconductor alloy, and the results are correlated with energy-dispersive x-ray measurements. A finite-element modeling approach is developed based on the experimentally monitored melting dynamics and composition gradient results for understanding and prediction of the dynamics.
CRIS-Team Scopus Importer:2021-06-29